Quantitative Evaluation of Muscle Function, Gait, and Postural Control in People Experiencing Critical Illness After Discharge From the Intensive Care Unit. Issue 1 (23rd October 2017) - Kiriella, Jeevaka B; Araujo, Tamara; Vergara, Martin; Lopez-Hernandez, Laura; Cameron, Jill I; Herridge, Margaret; Gage, William H; Mathur, Sunita
Abstract: Background: The path to recovery of muscle strength and mobility following discharge from the intensive care unit (ICU) has not been well described. Objective: The study objective was to quantify muscle function, gait, and postural control at 3 and 6 months after discharge in people who were recovering from critical illness and who were ventilated for 7 days or more. Design: This was a nested longitudinal study with continuous inclusion of individuals over a 2-year period and with age- and sex-matched controls. Methods: Twenty-four people were tested at 3 months after ICU discharge; 16 of them (67%) were reevaluated at 6 months (post-ICU group). Healthy controls (n = 12) were tested at a single time point. Muscle function of the knee extensors (KEs), plantar flexors (PFs), and dorsiflexors (DFs) was assessed on a dynamometer. Gait was measured using an electronic walkway, and postural control was measured with 2 portable force plates. Results: Muscle weakness was observed across all muscle groups at 3 months, with the greatest strength reductions in the ankle PFs (45%) and DFs (30%). Muscle power was reduced in the PFs and DFs but was not reduced in the KEs. Gait in the post-ICU group was characterized by a narrower step, longer stride, and longer double-support time than in the controls. Improvements were found in KE strength and in stride time and double-support time during gait at 6 months. Leg muscle strength and power had moderate associations with gait velocity, step width, and stride length ( r = .44–.65). Limitations: The small heterogeneous sample of people with a high level of function was a limitation of this study. Conclusions: Muscle strength and power were impaired at 6 months after ICU discharge and were associated with gait parameters. Future studies are needed to examine the role of muscle strength and power training in post-ICU rehabilitation programs to improve mobility.